THE ROLE OF FICTION IN TEACHING THE RUSSIAN LANGUAGE IN EDUCATIONAL INSTITUTIONS OF THE MIA (International journal of artificial intelligence, 2026)
This article explores the multifaceted role of fiction in teaching the Russian language within the specialized educational institutions of the Ministry of Internal Affairs (MIA). The author argues that language instruction for future law enforcement officers must transcend basic grammatical proficiency to encompass psychological depth and ethical fortitude. By integrating classical and contemporary Russian literature—notably the works of Dostoevsky, Tolstoy, and Pushkin—the pedagogical framework addresses the unique demands of police work, such as conflict de-escalation, professional empathy, and moral decision-making. The study highlights how literary texts provide authentic linguistic input, enabling cadets to master various speech registers essential for communicating with diverse social groups. Furthermore, the article examines the logistical challenges of implementing such a curriculum within rigorous military-style schedules and proposes innovative methodological strategies, including the use of "micro-texts" and comparative linguistic analysis, to ensure the professional and ethical development of highly skilled law enforcement personnel.